2014
DOI: 10.4103/1305-7456.143627
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of ozonated water, sodium hypochlorite and chlorhexidine gluconate in primary molar root canals

Abstract: Objective:The aim was to determine the antimicrobial effect of ozonated water, ozonated water with ultrasonication, sodium hypochloride and chlorhexidine (CHX) in human primary root canals contaminated by Enterococcus faecalis (E. faecalis).Materials and Methods:Fifty-eight extracted human primary molar teeth were used. Crowns were cut off using a diamond saw under water-cooling. One hundred roots were obtained and mechanically prepared. The roots were then sterilized by autoclaving in water for 15 min at 121°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 27 publications
0
14
0
6
Order By: Relevance
“…Different solutions are used for root canal irrigation. NaOCl is the most preferred irrigation solution because it is an organic solvent, antiseptic, has low surface tension, can easily diffuse to dentin walls, shows good residual effect, and has a long shelf life (Frais et al ., ; Goztas et al ., ; Tulsani et al ., ). The cleaning and antimicrobial effect of EDTA and NaOCl combined is superior to using a single solution (Niu et al ., ; Kalyoncuoglu and Demiryurek, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different solutions are used for root canal irrigation. NaOCl is the most preferred irrigation solution because it is an organic solvent, antiseptic, has low surface tension, can easily diffuse to dentin walls, shows good residual effect, and has a long shelf life (Frais et al ., ; Goztas et al ., ; Tulsani et al ., ). The cleaning and antimicrobial effect of EDTA and NaOCl combined is superior to using a single solution (Niu et al ., ; Kalyoncuoglu and Demiryurek, ).…”
Section: Introductionmentioning
confidence: 99%
“…Ozone's oxidizing power is exerted specifically on polyunsaturated fatty acids of the bacterial membrane, increasing oxygen delivery to tissues and modulating the immune system, thereby improving and accelerating tissue repair. According to Goztas et al .,[ 33 ] the advantages of ozone in the aqueous phase include lack of mutagenicity, rapid microbicidal effects, and ease of handling. The authors also reported that ozonated water shows no cytotoxicity and is highly biocompatible compared with other antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluando la eficacia antimicrobiana del extracto de hoja de guayaba y aloe vera en comparación con hipoclorito de sodio, clorhexidina y QMix empleados como irrigantes de conductos radiculares, observamos que si bien el extracto de hojas de guayaba y el extracto áloe vera poseen acciones antibacterianas y antioxidantes contra patógenos orales Candida Albicans y Enterococus Faecalis, los resultados muestran al QMix como una nueva propuesta para la irrigación de conductos relacionando su eficacia antibacteriana con su composición (11) .…”
Section: Características De Las Soluciones Desinfectantes Irrigadorasunclassified